Near-term benefits from investment in climate adaptation complement long-term economic returns from emissions reduction - Lei Duan; Angelo Carlino; Ken Caldeira (Communications Earth & Environment)
Abstract Previous studies have suggested that a combined strategy using both emissions abatement and climate adaptation can improve economic outcomes. Here, using a parsimonious economic-climate assessment model, we have shown that, relative to investment in abatement, adaptation has a much shorter timescale for economic return. Adaptation deployed in conjunction with abatement allows earlier benefits compared to investment in abatement alone. Our results provide evidence of greater net benefit with complementary investments in abatement reducing long-term climate damage and investments in adaptation reducing near-term damage. The timescale of return on investment in abatement is strongly influenced by economic discount rates, whereas the timescale of return on investment in adaptation is strongly influenced by the capital depreciation timescale. Higher levels of abatement investment associated with stringent emissions reduction constraints can reduce returns on adaptation investment. Even so, our results indicate greater near-term and long-term net benefits when investing in both abatement and adaptation.